A Miniaturised UWB FSS With Stop-Band Characteristics For EM Shielding Applications - Al-Gburi, Ahmed Jamal Abdullah; Mohd Ibrahim, Imran; Zakaria, Zahriladha; Zeain, Mohammed Yousif; Ahmad, Khalid Subhi; Abdulhameed, M. K.; Saeidi, Tale (Wydawnictwo SIGMA-NOT, 2021)
This paper aims to present a miniaturised and new design of ultra-wideband (UWB) frequency selective surface (FSS) with stopband characteristics for electromagnetic (EM) shielding applications. The modelled FSS used the integration of a two parallel conductive metallic patch with a circular loop structure. The FSS provided a UWB stopband filter response covering a bandwidth of 10.5 GHz, for frequencies from 2.2 GHz to 12.7 GHz. The proposed FSS had a compact physical dimension of 5 mm × 5 mm × 1.6 mm, with a printed array of 19 × 19 FSS unit cells. An equivalent circuit configuration (ECC) was used to verify the FSS unit cell structure’s performance. The proposed FSS was identified to contribute towards independent polarisation for obliques incidences transverse electric (TE) and transverse magnetic (TM) polarisations from 0° to 20°. Besides, the performance of the proposed FSS is stable over a wide range of incident angles for TE and TM polarisations